The Role of Technology in Enhancing Public Health Preparedness for Disasters - Aninda Tanggono; Irfani Prajnaparamita; Prita Aulia Nastaghfiruka (Riwayat: Educational Journal of History and Humanities, 2025)
In recent years, the increasing frequency and severity of natural disasters have highlighted the critical need for enhanced public health preparedness. This literature review examines the role of technology in improving public health responses to disasters. Various technological advancements, including data analytics, geographic information systems (GIS), mobile applications, and telemedicine, have been identified as pivotal in enhancing preparedness and response efforts. Data analytics enables the timely collection and analysis of health information, facilitating informed decision-making during emergencies. GIS tools provide essential mapping capabilities that aid in resource allocation and risk assessment, allowing health officials to identify vulnerable populations and areas at high risk. Mobile applications enhance communication and information dissemination, ensuring that communities receive real-time updates and guidance during disasters. Furthermore, telemedicine has emerged as a vital tool for maintaining healthcare access when traditional services are disrupted. This review also discusses the challenges associated with technology integration, including issues of equity, privacy, and the need for training among healthcare professionals. Ultimately, the findings underscore the importance of leveraging technology to strengthen public health systems and improve disaster preparedness. By adopting innovative technological solutions, public health authorities can enhance their ability to respond effectively to disasters, ultimately safeguarding the health and well-being of communities.